How to present L2 Chinese words effectively for learning: Exploring learning outcomes and learner perceptions - Xuehong (Stella) He (Studies in Second Language Acquisition, 2024)
Second language (L2) research on input manipulation has focused mainly on increasing the salience of target structures, but presentation formats of L2 input can be another important aspect for manipulation. This study compared the horizontal, vertical, and adjacent formats for presenting the characters, pinyin, and English meaning of L2 Chinese vocabulary, by recruiting 69 English native speakers to study 30 Chinese words in these formats. Learning outcomes were indexed with vocabulary gain scores from pretest to posttest. Learner perceptions of the learning process were recorded with ratings and reasons for preference among these formats. The quantitative results showed the adjacent format generally led to higher gain scores than the other two formats and that L2 proficiency also contributed positively. To learners, the adjacent format was the least preferred, but preference ratings were not associated with gain scores. The qualitative findings suggested format familiarity and layout features as main factors of learner preference.